Answer:
[tex]A = 2B[/tex]
[tex]A + B = 25[/tex]
Step-by-step explanation:
Given
The first statement implies that:
[tex]X = A + B[/tex] i.e the components of X
Reading further, we have:
[tex]X = 45[/tex] ---- The mass of X
[tex]A = 2B[/tex] --- The relationship between [tex]A\ and\ B[/tex]
Required
Two equations to represent the scenario
The two equations are:
[tex]A = 2B[/tex] --- The relationship between [tex]A\ and\ B[/tex]
[tex]X = A + B[/tex] i.e the components of X
Substitute 25 for X in the second equation
[tex]25 = A + B[/tex]
[tex]A + B = 25[/tex]
So, the equations are:
[tex]A = 2B[/tex]
[tex]A + B = 25[/tex]